Things unchanged: online and offline practice of an Indian first-year composition curriculum - Kim, Jooyoung (Frontiers in Education, 2025)
The shape of classroom and learning in higher education has transformed during the COVID-19 pandemic in a way of increasing learners' socialization and connectedness in the virtual setting. This study examines 4 years' work of design, development, and refinement for a two-semester-long undergraduate first-year writing (FYW) course during and after the pandemic, throughout the transition from online to offline mode in India. Undergraduate FYW courses in India have multiple functions such as learning English as a second language and academic/social integration, and they were placed in an optimal position to compensate the lack of physical interactions and socialization during the pandemic. First, we discuss three designing principles that have been constant from the establishment of the curriculum: authentic learning with digital literacy, maximizing socialization, and empowering students' voice. Second, an online survey was conducted to measure students' perception and perspective on their adapted learning environments—online only, mostly online, mostly offline, and offline only conditions. The results indicate that the offline mode was overall more satisfactory for writing practice and learning, while some functions in the online mode provided meaningful support for an interactive writing experience.